Efecto de la temperatura y tiempo de almacenamiento sobre la concentracion de fructooligosacáridos en yacón fresco (smallanthus sonchifolius) - Zamudio Vejarano, Daniel Leopoldo (2015)
The present research has as an objective to evaluate the effect of temperature and storage time in the yacon concentration of Fructooligosaccharides (FOS) and yacon humidity in fresh product. A factorial design 3 by 2, with 3 repetitions for each treatment, was used. The yacon was storage at 8, 20 and 30°C by a time of 4, 7 and 14 days accord with the response at the experimental design. Humidity and Fructooligosaccharides percent present in the samples was analyzed, at the same time 3 repetitions where made for each of the samples. It was possible to observe that the yacon FOS contain decrease when the storage temperature increase, at the same time, it decrease when the storage time increase. In the case of the humidity percent decrease for the storage temperature effect (more temperature, less humidity percent) and the storage time effect (more storage time, less humidity percent). For all of these, we can conclude that the dependent variables, the storage temperature, the storage time (in days), and the interaction of both, affect in a significant way to the humidity percent and the Fructooligosaccharides percent in the yacon, and analyzing the results, it is recommended a storage temperature of 8°C, with a yacon initial humidity between 80 and 90 percent, to maintain for a longest time the yacon FOS contain.